CHBMLI based DSTATCOM for power quality improvemt in a three-phase three-wire distribution system with PI controller - Madhu Babu, Thiruveedula; Chenchireddy, Kalagotla; Sreevarsha, Kama; Praveen, Badudhala; Mohammad, Thanveer; Kashinadh, Ganji (Institute of Advanced Engineering and Science, 2024)
This paper presents a cascaded h-bridge (CHB) multilevel inverter (MLI) based MLI based distribution static synchronous compensator (DSTATCOM). The main objective of this paper is to reduce source current harmonics in the distribution system by using a cascade H-bridge multilevel inverter (CHBMLI) as DSTATCOM with a proportional-integral (PI) controller. The PI controller compensates reactive power, reduces source current harmonics, and maintains the unity power factor in the distribution system. The conventional two-level inverter-based DSTATCOM has many disadvantages such as high total harmonic distortion (THD), and high switching stress power semi-conductor devices, suitable for only low-power applications. This paper to overcome these drawbacks by using MLI-based DSTATCOM. The proposed system simulations are verified in MATLAB/Simulink software. The verified results are source current, load current, and compensating current.